ANALISIS BIAYA BAHAN BAKU, BIAYA TENAGA KERJA DAN BIAYA OVERHEAD PABRIK TERHADAPHARGA POKOK PRODUKSI PADA PABRIK TAHU BEJO DI BUKUR - Sanrully, Muhamad Ichwan Ade; Winarko, Sigit Puji; Zaman, Badrus (Universitas Nusantara PGRI Kediri, 2022)
This research motivated by understanding of the production cost calculation at the Tahu Bejo Factory. PuRpose of this research to how importance for determining cost of production in the food industry especially in the Tahu Bejo Factory. Meanwhile to determining cost of production this research uses two methods the first one is full costing method and the second one is variable costing method. This research used quantitative descriptive approach by interviews techniques, literatures studies and documentation from source person by obtaining data of raw material costs, labor costs and factory overhead costs so researcher gaining a lot of information to continue the research. Results of this research is the calculation of production cost performed by factory is higher while compared with calculation using full costing method and variable costing method. In addition there have differences for both methods while using full costing method, cost is higher than the calculation using variable costing method. Keywords: Material Costs, Labour Costs and Overhead Costs Factory.